A controlled clinical trial investigating the effects of stretching and compression exercises on electromyography of calf muscles in chronic LBP patients with a deep gluteal syndrome - MohammadBagher Shamsi; Maryam Mirzaei; Kevork Hopayian (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background In deep gluteal syndrome (DGS), the piriformis muscle could impinge the sciatic nerve. The FAIR (flexion adduction internal rotation) test is a provocation test used to identify sciatic nerve irritation caused by this muscle. Compression and stretching exercises are usually prescribed to treat this syndrome. The aim of this study was to compare the effects of these two treatments on surface electromyography (sEMG) of the gastrocnemius and tibialis anterior in patients with low back pain (LBP) and DGS. Materials and methods Forty-five participants were allocated to three groups of stretching exercise, compression or control. In addition to 15 min of heat and 15 min of electrical nerve stimulation for pain relief, participants in the compression exercise (CE) group received self-compression exercise, those in the stretching exercise (SE) group received self-stretching exercise and those in the control group received no extra interventions. For the two intervention groups, three sets of two minutes of exercise with two minutes of rest in between were applied. The sEMG amplitude values of the gastrocnemius and tibialis anterior muscles of the affected buttock side of any one group while performing the FAIR test were compared to the others. Pain and disability were assessed and the changes were compared between the two groups. Results After the intervention period, no group demonstrated a change in the sEMG of the gastrocnemius or tibialis anterior muscles (p > 0.05). There was no difference in the change in this variable between groups (Mean difference (95% CI) of gastrocnemius was ranged over= -4.04 to 7.72 (-19.44 to 23.14); p = 0.603); (Mean difference (95% CI) of tibialis anterior muscles was ranged from − 2.44 to -6.43 (-18.28 to 9.31); p = 0.550).; Pain and disability also decreased significantly in all three study groups (p < 0.05). However, only the disability of patients who performed stretching exercises improved compared to the compression exercise group (Mean difference (95% CI) = -12.62 (-20.41 to -4.38); p = 0.009). Conclusion Neither stretching nor compression exercises altered the sEMG of the gastrocnemius and tibialis anterior muscles in patients with DGS. Furthermore, performing stretching exercises improved disability compared to the other interventions. Trial registration The trial was retrospectively registered in the Iranian Registry of Clinical Trials ( www.irct.ir ) on 10/01/2017 as IRCT201604178035N4. URL of the record: https://en.irct.ir/trial/8473 .